Mutilating neuropathic ulcerations in a chromosome 3q13-q22 linked Charcot-Marie-Tooth disease type 2B family. Issue 6 (June 1997) - De Jonghe, P; Timmerman, V; FitzPatrick, D; Spoelders, P; Martin, J J; Van Broeckhoven, C
Abstract : BACKGROUND: Charcot-Marie-Tooth disease type 2 (CMT2) or hereditary motor and sensory neuropathy type II (HMSN II) is an inherited axonal neuropathy of the peripheral nervous system. Three autosomal dominant CMT2 loci have been located on chromosomes 1p35-p36 (CMT2A), 3q13-q22 (CMT2B), and 7p14 (CMT2D) indicating that CMT2 is a genetically heterogeneous disorder. METHODS: A CMT2 family was examined for linkage to the CMT2A, CMT2B, and CMT2D loci using short tandem repeat polymorphisms. RESULTS: Suggestive evidence for linkage to 3q13-q22 was found. Recombinations occurred with markers D3S1769 and D3S1267 indicating that the CMT2B locus is located distal to D3S1267 and resides in an interval of 25 cM. Some patients in this family have pronounced sensory disturbances leading to poorly healing ulcerations. CONCLUSIONS: These unusual sensory signs for CMT were also noted in the only other CMT2B family reported so far, suggesting a distinct clinical phenotype for CMT2B. Exclusion of the locus for hereditary sensory neuropathy type I (HSN I) on chromosome 9q22 indicates that HSN I with mild motor symptoms and CMT2 with prominent sensory abnormalities are not allelic.